2020
DOI: 10.1016/j.parepi.2020.e00184
|View full text |Cite
|
Sign up to set email alerts
|

Malaria among febrile neonates attending the neonatology unit of the Bamenda regional hospital

Abstract: Malaria remains the leading cause of infant’s mortality in malaria endemic countries like Cameroon. Due to the presence of passively acquired maternal antibodies, malaria in neonates was thought to be scarce. Consequently routine malaria checks are mostly not considered for febrile neonates. Nonetheless findings from malaria endemic areas have proven that malaria in neonates is not uncommon. This study is therefore designed to evaluate malaria among febrile neonates attending the neonatology unit of the Bamend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…[19,21,22] All the children had their blood tested for malaria parasite compared to 25% tested in an earlier Nigerian report in 2018. [17] The prevalence of neonatal malaria in the current study was 60.4% (29/48); this is comparable to 43.7% in Port Harcourt, Nigeria [23] but higher than figures from Cameroon (17.5%), [24] Gambia (13.3%), [20] and Jos, Nigeria (5.3%). [25] Several studies have discussed the impact of seasonality and diagnostic method on reported prevalence rates.…”
Section: Numbers In Parentheses Are Percentages Of Variables With Par...supporting
confidence: 50%
“…[19,21,22] All the children had their blood tested for malaria parasite compared to 25% tested in an earlier Nigerian report in 2018. [17] The prevalence of neonatal malaria in the current study was 60.4% (29/48); this is comparable to 43.7% in Port Harcourt, Nigeria [23] but higher than figures from Cameroon (17.5%), [24] Gambia (13.3%), [20] and Jos, Nigeria (5.3%). [25] Several studies have discussed the impact of seasonality and diagnostic method on reported prevalence rates.…”
Section: Numbers In Parentheses Are Percentages Of Variables With Par...supporting
confidence: 50%